Hubungan Antara Durasi Penggunaan Gadget dan Kemampuan Imajinasi Siswa Kelas II Sekolah Dasar (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
The focus of this research is to analyze the correlation between the duration of gadget use and the imaginative abilities of second-grade elementary school students. A quantitative approach was utilized with a correlational survey method involving 32 students from SDN Pekayon 16 Pagi as the sample. Data were collected through a validated open questionnaire regarding validity and consistency. The analysis findings indicate a negative relationship between the duration of gadget use and students' imaginative abilities. The longer the duration of gadget use (≥60 minutes/day), the lower the students' imaginative abilities, and vice versa. These findings highlight the urgency of parental monitoring in controlling the duration of gadget use as well as the selection of educational content. This research contributes to understanding the impact of technology on children's cognitive development, particularly in the area of imagination.